Transcatheter closure of interatrial communications with a modified umbrella device. - Redington, A N (1994)
OBJECTIVE--To show the institutional experience of closure of interatrial communications with a modified umbrella device. DESIGN--Descriptive study of all patients in whom transcatheter umbrella closure of interatrial communications has been attempted. SETTING--A tertiary referral centre. PATIENTS--16 patients with 17 interatrial communications of various types. INTERVENTIONS--Transcatheter placement of a modified Rashkind umbrella occluder. RESULTS--Two procedural failures due to venous access problems. Two placement failures needing early surgical repair. 13 successful placements in 12 patients. CONCLUSIONS--The modified Rashkind umbrella can successfully be used to close both iatrogenic and naturally occurring interatrial communications, particularly those present after the Fontan procedure.